Extraction and Characterization of New Cellulose Fiber from the Agrowaste of Lagenaria Siceraria (Bottle Guard) Plant - Saravanan, N.; Sampath, P.S.; Sukantha, T.A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This article explores the extraction and characterization of natural fiber from the agro-waste of Lagenaria siceraria (LS) plant stem (commonly known as „bottle guard‟) for the first time. The extracted fiber from the waste stems has high cellulose content (79.91 %) with good tensile strength (257–717 MPa) and thermal stability (withstand up to 339.1°C). The immense percentage of crystalline index (92.4%) with the crystalline size (7.2 nm) as well as low density (1.216 g/cm3) of the LS fiber renders their possibilit